Bisphenol S and Bisphenol A Cyanate Ester/Barium Metaborate Composites - KAHRAMAN, MEMET VEZİR (WILEY, 2016)
The aim of this study was to improve thermal stability and surface properties of bisphenol A dicyanate ester (BADCy) by adding bisphenol S dicyanate ester (BSDCy) and Ba(BO2)(2). Bisphenol S and bisphenol A cyanate ester/barium metaborate composites having various ratios of BADCy, BSDCy, and Ba(BO2)(2) were prepared. Thermal stability of the samples was evaluated by thermogravimetric analysis and differential scanning calorimetry. Hydrophobicity of the samples was determined by the contact angle measurements. The samples were characterized with the following analysis; gel content, water absorption capacity. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy. The obtained results prove that the cyanate ester containing sulfonyl/Ba(BO2)(2) composites have good thermal and surface properties and they can be used in many applications such as electronic devices, materials engineering, and other emergent. (C) 2014 Society of Plastics Engineers
Keywords: ESTER RESIN